Electron paramagnetic resonance of a copper doped [(CH3)2NH2][Zn(HCOO)3] hybrid perovskite framework. Issue 17 (20th April 2018) - Šimėnas, Mantas; Ciupa, Aneta; Usevičius, Gediminas; Aidas, Kęstutis; Klose, Daniel; Jeschke, Gunnar; Mączka, Mirosław; Völkel, Georg; Pöppl, Andreas; Banys, Jūras
Abstract : We present an EPR study of the structural phase transition in a copped doped dimethylammonium zinc formate hybrid perovskite framework. Abstract : We report a continuous-wave (CW) and pulse electron paramagnetic resonance (EPR) as well as pulse electron nuclear double resonance (ENDOR) study of Cu 2+ doped [(CH3 )2 NH2 ][Zn(HCOO)3 ] hybrid perovskite which exhibits a structural phase transition. The multifrequency (X, Q and W-band) CW EPR measurements allow the temperature evolution of the Cu 2+ ion local environment to be studied. The spectrum of the ordered (low-temperature) phase reveals an axially distorted octahedral Cu 2+ site confirming the successful replacement of the Zn 2+ ions and formation of the CuO6 octahedra. The CW EPR spectrum of the disordered (high-temperature) phase shows an additional broad line which gradually diminishes on cooling. The EPR linewidth of the axially symmetric Cu 2+ ion site exhibits an anomaly at the phase transition point and Arrhenius-type behavior in the disordered phase. The temperature dependent Cu 2+ spin Hamiltonian parameters change abruptly at the phase transition point indicating a strong first-order character of the transition. The X-band pulse ENDOR spectrum of the ordered phase reveals several protons in the vicinity of the Cu 2+ center.